Weathering the empire: Meteorological research in the early nineteenth-century Straits Settlements - WILLIAMSON, Fiona (Institutional Knowledge at Singapore Management University, 2015)
This article explores meteorological interest and experimentation in the early history of the Straits Settlements. It centres on the establishment of an observatory in 1840s Singapore and examines the channels that linked the observatory to a global community of scientists, colonial officers and a reading public. It will argue that, although the value of overseas meteorological investigation was recognized by the British government, investment was piecemeal and progress in the field often relied on the commitment and enthusiasm of individuals. In the Straits Settlements, as elsewhere, these individuals were drawn from military or medical backgrounds, rather than trained as dedicated scientists. Despite this, meteorology was increasingly recognized as of fundamental importance to imperial interests. Thus this article connects meteorology with the history of science and empire more fully and examines how research undertaken in British dependencies is revealing of the operation of transnational networks in the exchange of scientific knowledge.